Ultrasensitive colorimetric assay of cadmium ion based on silver nanoparticles functionalized with 5-sulfosalicylic acid for wide practical applications1. Issue 10 (21st May 2015) - Jin, Weiwei; Huang, Pengcheng; Wu, Fangying; Ma, Li-Hua
<x xml:space="preserve">Abstract</x> A simple, low-cost yet very sensitive and selective colorimetric assay for Cd2+ is introduced based on 5-sulfosalicylic acid functionalized silver nanoparticles.